2009
DOI: 10.1007/s00394-009-0053-7
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of adherence to a Mediterranean-type diet in the PREDIMED trial

Abstract: Background: Determinants of dietary changes obtained with a nutritional intervention promoting the Mediterranean diet have been rarely evaluated.Aim of the study: To identify predictors of higher success of an intervention aimed to increase adherence to a Mediterranean diet (MeDiet) in individuals at high cardiovascular risk participating in a trial for primary prevention of cardiovascular disease: the PREDIMED (PREvención con DIeta MEDiterránea) trial. Candidate predictors included demographic and socioeconom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
31
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 35 publications
8
31
0
Order By: Relevance
“…men vs. women). In fact, it has been demonstrated that some strategies aimed at improving dietary habits may have different impacts in men and in women (25)(26)(27). Results from the present study are therefore relevant since they indicate for the first time that an intervention based mainly on exposure to the MedDiet may be effective for increasing adherence, irrespective of gender, as suggested by the increase in the MedScore in both men and women at the 6-month follow-up visit compared to baseline.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…men vs. women). In fact, it has been demonstrated that some strategies aimed at improving dietary habits may have different impacts in men and in women (25)(26)(27). Results from the present study are therefore relevant since they indicate for the first time that an intervention based mainly on exposure to the MedDiet may be effective for increasing adherence, irrespective of gender, as suggested by the increase in the MedScore in both men and women at the 6-month follow-up visit compared to baseline.…”
Section: Discussionmentioning
confidence: 57%
“…These differences may influence the quality of diet and the degree of adherence to healthy dietary recommendations (24). In the context of the MedDiet, previous studies found evidence that some nutritional strategies concerning adherence and dietary intakes have a different impact according to gender; some favoring men (25,26) whereas others impacting women more efficiently (27).…”
Section: Introductionmentioning
confidence: 99%
“…The strategic cherry picking of the best elements of Mediterranean traditions has certainly created a useful 'whole diet model' that has had beneficial impact on populations in Northern Europe [44,45]. Numerous studies illustrate that the adoption of food choices typical of Mediterranean countries may be beneficial in metabolic and vascular diseases [46]. Ironically, although overall adherence to this 'model' of eating has decreased within the Mediterranean, in Northern Europe there has been growing acceptance of the diet pyramid [11,31,47].…”
Section: Mediterranean Diet As a Global Health Toolmentioning
confidence: 99%
“…Previous trials have shown the usefulness of appreciating the macronutrient composition of foods for demonstrating adherence to nutrient targets [10] and subsequent health benefits [26]. For example, virgin olive oil (1L/week) and mixed nuts (30g/day) were used in the PREDIMED Study to enable participants to achieve the Mediterranean-style diet being tested [17]. However, the study design included the free provision of specific high fat foods and, therefore, did not provide evidence for free-living food choices in response to advice alone.…”
Section: Discussionmentioning
confidence: 99%
“…Studies demonstrating favourable modifications to the overall food pattern have relied on the free provision of foodstuffs to ensure achievement of dietary targets. For example, a Mediterraneanstyle diet was achieved in the PREDIMED study by providing participants with regular amounts of palatable key high fat foods [17], but its application may be difficult to replicate in free-living settings. In contrast, general approaches to advice, for example, choose low fat foods in ad libitum fashion do not appear to support significant changes to the macronutrient profile [18,19].…”
Section: Introductionmentioning
confidence: 99%